Kepemimpinan Guru Sebagai Role Model Di Sekolah - Ima Rahmawati; Siti Lutfiatul Hasanah; Nurdin Fahrurrobi (JURNAL KAJIAN ISLAM MODERN, 2023)
This study aims to examine teacher leadership with a literature study approach. The essence of leadership in the classroom is the ability to influence and move students to achieve learning goals in class. The teacher can also become a leader during the learning process, both inside and outside the classroom. The goal is that the teacher is expected to be able to lead students according to the leadership function related to the learning objectives to be achieved. A teacher must also understand good leadership models, this is because a good learning process is determined by a leadership style that is identical to the teacher's leadership model in the learning process in the classroom. The learning process at the elementary school level is very different from that at the secondary level, especially in terms of conveying learning material to students. Automatically the teacher's leadership style must also be adapted to the situation of students at the elementary school level. Keywords: Teacher leadership, teacher's role, leadership